Review article: Mucosa-associated lymphoid tissue (MALT)-type lymphoma of ocular adnexa. Biology and treatment. (April 2016) - Annibali, Ombretta; Sabatino, Francesco; Mantelli, Flavio; Olimpieri, Odoardo Maria; Bonini, Stefano; Avvisati, Giuseppe
Highlights: A review of MALT type lymphoma of ocular adnexa is proposed. Over the last decades, we have assisted to an increase in the incidence of primary ocular adnexa lymphomas (POALs). The ocular tissue biopsy, before the initiation of the appropriate treatment, is mandatory and necessary for a correct diagnosis of POALs. Among the POALs, the most common is the primary extra nodal lymphoma of MALT-type (POAML). The clinical manifestations are heterogeneous and its management requires a multidisciplinary approach involving ophthalmologists, hematologists and radiotherapists. Abstract: Over the last decades, we have witnessed an increase in the incidence of primary ocular adnexa lymphomas (POALs) probably because advances in imaging techniques have enabled precise biopsies of the tumors. The ocular tissue biopsy, before the initiation of the appropriate treatment, is mandatory and necessary for a correct diagnosis of POALs by the use of immunophenotyping and a correct molecular classification. Only in a minority of cases the ocular adnexa are secondarily affected by a systemic disease. Among the POALs, the most common is the primary extra nodal lymphoma of MALT-type (POAML). POAML is rarely symptomatic in the early phase of the disease. As a consequence, often we see a delay in ophthalmic consultations and diagnosis. The clinical manifestations are heterogeneous and its management requires a multidisciplinary approach involving ophthalmologists, hematologists and radiotherapists.